Metode Pembelajaran E-Learning Menggunakan Technology Acceptance Modelling (TAM) Untuk Pembelajaran Akuntansi - Johandri Iqbal; Arisman - (InFestasi, 2018)
This study develops E-learninglearning model. By applying E-learninglearning design, it facilitates lecturer and student to expand supporting course on their own. E-learningsystem design uses technology acceptance model concept (TAM) which is a technology and information system acceptance model will be used by the user. The construct in technology acceptance mode is perceived usefulness, perceived ease of use, attitude towards behavior, behavioral intention, and actual technology use. Hypothesis test used structural equation modeling (SEM). By testing the validity and reliability, Model fit criteria, Output Laten Variable coefficients, Output Indirect and total Effects, seven hypothesis which would be examined, five hypothesis are accepted and two hypothesis are rejected.